Correlations of low‐field NMR and variable‐field NMR parameters with osteoarthritis in human articular cartilage under load. (24th May 2017) - Rössler, Erik; Mattea, Carlos; Saarakkala, Simo; Lehenkari, Petri; Finnilä, Mikko; Rieppo, Lassi; Karhula, Sakari; Nieminen, Miika T.; Stapf, Siegfried
Abstract : NMR experiments carried out at magnetic fields below 1 T provide new relaxation parameters unavailable with conventional clinical scanners. Contrast of T 1 generally becomes larger towards low fields, as slow molecular reorientation processes dominate relaxation at the corresponding Larmor frequencies. This advantage has to be considered in the context of lower sensitivity and frequently reduced spatial resolution. The layered structure of cartilage is one example where a particularly strong variation of T 1 across the tissue occurs, being affected by degenerative diseases such as osteoarthritis (OA). Furthermore, the presence of 1 H‐ 14 N cross‐relaxation, leading to so‐called quadrupolar dips in the 1 H relaxation time dispersion, provide insight into the concentration and mobility of proteoglycans and collagen in cartilage, both being affected by OA. In this study, low‐field imaging and variable‐field NMR relaxometry were combined for the first time for tissue samples, employing unidirectional load to probe the mechanical properties. 20 human knee cartilage samples were placed in a compression cell, and studied by determining relaxation profiles without and with applied pressure (0.6 MPa) at 50 μm in‐plane resolution, and comparing with volume‐averaged T 1 dispersion. Samples were subsequently stored in formalin, prepared for histology and graded according to the Mankin score system. Quadrupolar dips and thickness change under load showed the strongest correlation with Mankin grade. Average T 1 and change of maximum T 1 under load, as well as its position, correlate with thickness and thickness change. Furthermore, T 1 ( ω ) above 25 mT was found to correlate with thickness change. While volume‐averaged T 1 is not a suitable indicator for OA, its change due to mechanical load and its extreme values are suggested as biomarkers available in low‐field MRI systems. The shape of the dispersion T 1 ( ω ) represents a promising access to understanding and quantifying molecular dynamics in tissue, pointing toward future in vivo tissue studies. Abstract : Low‐field MRI and variable‐field NMR relaxometry were combined, for the first time, to study human knee cartilage samples. The shape of the frequency‐dependent T1, in particular the quadrupolar dips between 50 and 70 mT, were shown to correlate with the degree of osteoarthritis degeneration. Mechanical load characteristically affects the distributions of relaxation times across the tissue.